When should state secrets stay secret? accountability, democratic governance, and intelligence - Lester, Genevieve 1973- (Cambridge Univ. Press, 2015)
Contrary to popular assumption, the development of stronger oversight mechanisms actually leads to greater secrecy rather than the reverse. When Should State Secrets Stay Secret? examines modern trends in intelligence oversight development by focusing on how American oversight mechanisms combine to bolster an internal security system and thus increase the secrecy of the intelligence enterprise. Genevieve Lester uniquely examines how these oversight mechanisms have developed within all three branches of government, how they interact, and what types of historical pivot points have driven change among them. She disaggregates the concept of accountability into a series of specified criteria in order to grapple with these pivot points. This book concludes with a discussion of a series of normative questions, suggesting ways to improve oversight mechanisms based on the analytical criteria laid out in the analysis. It also includes a chapter on the workings of the CIA to which a number of CIA officers contributed